Can Underutilized Tropical Fruits Meet the Nutritional Requirements of Rural Indonesia? - Krishnanunni Mavinkal Ravindran; Philippa J. Jones; Mark Rayment (Indonesian Journal of Innovation and Applied Sciences (IJIAS), 2021)
Tropical fruits form a potential source of micronutrients. However, a lot of these fruit species remain underutilized in developing countries. This study explores the potential of underutilized tropical fruits in Kalimantan, Indonesia, in meeting the micro-nutrient requirements of its populace. The study employs focus group discussions and a systematic literature search and review process to gather data.79% of the species studied were profuse in at least one essential micronutrient, and 53% of the species contain at least one micronutrient of priority concern in high concentration. No nutritional information was available for 26% of the reviewed species, and 40% of the species for which information is available in the literature lacked data on at least one priority micro-nutrient. Simultaneous fruiting of priority micro-nutrient rich species occurring in the different agroecosystems of Kalimantan, namely limbo gardens, homesteads, and forests, corroborates the importance of landscape diversity in meeting the year-round nutritional needs of its people. Given how the Covid19 pandemic has impacted people's food security, it is essential to address these knowledge gaps to aid the ongoing efforts to reshape our food systems in the future.